Graft preservation solution DuraGraft® alleviates vascular dysfunction following in vitro ischemia/reperfusion injury in rats - Korkmaz-İçöz, Sevil; Ballikaya, Belinda; Soethoff, Jasmin; Kraft, Patricia; Sayour, Alex Ali; Radovits, Tamás; Loganathan, Sivakkanan; Karck, Matthias; Szabó, Gábor; Veres, Gábor (Pharmaceuticals, 2021)
Vascular ischemia/reperfusion injury (IRI) in patients undergoing coronary artery bypass grafting can result in graft failure and the need for repeat revascularization procedures. DuraGraft® has been shown to protect structure and function in saphenous vein grafts against IRI. We compared the effect of DuraGraft® to saline solution on arterial grafts submitted to IRI. Rat thoracic aortic rings were harvested and immediately mounted in organ bath chambers (control, n = 7 rats) or underwent cold ischemic preservation either in saline (IR, n = 9 rats) or DuraGraft® (IR+Dura, n = 9 rats). Vascular function was measured ex vivo and immunohistochemistry was performed. Impaired maximum vasorelaxation (Rmax) to ACh in the IR-group compared to controls was ameliorated by DuraGraft®, indicating an improvement in endothelial function (Rmax to ACh (%): IR + Dura 73 ± 2 vs. IR 48 ± 3, p < 0.05). Additionally, decreased aortic ring sensitivity to ACh (pD2-value: -log 50% maximum response) seen after IR in the saline group was increased by DuraGraft® (pD2 to ACh: IR+Dura 7.1 ± 0.1 vs. IR 6.3 ± 0.2, p < 0.05). Impaired maximum contractile response to phenylephrine and high potassium chloride concentrations in the IR group compared to controls was significantly improved by DuraGraft®. DuraGraft® alleviates vascular dysfunction following IRI by reducing nitro-oxidative stress and the expression of ICAM-1, without leukocytes engagement.
Gesehen am 06.12.2021